Measurement of erythrocyte motions in microchannels by using a confocal micro-PTV system - Lima, Rui A. (2007)
Detailed knowledge on the motion of individual red blood cells (RBCs) flowing in microchannels is essential to provide a better understanding on the blood rheological properties and disorders in microvessels. Several studies on both individual and concentrated RBCs have already been performed in the past. However, all studies used conventional microscopes and also ghost cells to obtain visible trace RBCs through the microchannel. Recently, considerable progress in the development of confocal microscopy and consequent advantages of this microscope over the conventional microscopes have led to a new technique known as confocal micro-PIV. This technique combines the conventional PIV system with a spinning disk confocal microscope (SDCM). Due to its outstanding spatial filtering technique together with the multiple point light illumination system, this kind of microscope has the ability to obtain in-focus images with optical thickness less than 1 μm, a task extremely difficult to be achieved by using a conventional microscope. The main purpose of this paper is to investigate the ability of our confocal micro-PTV system to measure the motion of individual RBCs at different haematocrit (Hct) through microchannels.